Uji Sitotoksisitas Hidroksiapatit Cangkang Telur Ayam Ras (Gallus gallus) terhadap Sel Fibroblas Ligamen Periodontal Manusia - Devi Komala; Muhammad Nurul Amin; Yani Corvianindya Rahayu (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Periodontitis is an inflammation disease of the periodontal tissues surrounding the teeth, include periodontal ligament fibroblast cell. The recently researches developed tissue engineering concept to accelerate regeneration and proliferation periodontal ligament cells. One of the major components of tissue engineering is scaffold. The hydroxyapatite is biomaterial that can be used as scaffold. The egg shell has the potential biowaste to be a source of hydroxyapatite biomaterial. Before being applied as a scaffold in the medical field, cytotoxicity testing needs to be done. This study aimed to examine toxicity effect of egg shell hydroxyapatite in various concentration toward human periodontal ligament fibroblast cells. This study used human periodontal ligament fibroblast primary cells (5x103) in microplate 96 wells which divided into 7 groups, control cells, control media without cells and the treatment groups with concentration egg shell hydroxyapatite100 μg/ml, 75 μg/ml, 50 μg/ml, 25 μg/ml dan 25 μg/ml and incubated for 24 hours. Cytotoxicity test was conducted using MTT assay. Optical density values describe the viability of living cells and the readings were done using ELISA readers, subsequently the data were analyzed using One way ANOVA. The number of human periodontal ligament cells at all concentration showed that the percentage of cell life is more than 90%. Egg shell hydroxyapatite at all concentrations tested is not toxic toward human periodontal ligament fibroblas cells.